2013
DOI: 10.1680/geot.12.p.026
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of ball penetrometer in uniform single- and double-layer clays

Abstract: The spherical ball penetrometer is increasingly being used for profiling the undrained shear strength of soils in centrifuge and offshore site investigations. This paper reports the results from largedeformation finite-element (LDFE) analysis undertaken to provide insight into ball penetrometer behaviour during undrained vertical penetration through uniform and stratified clay deposits. The LDFE analyses simulated continuous penetration of ball penetrometers from the seabed surface. The results were validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…Merifield et al, 2009;White et al, 2010;Chatterjee et al, 2012;Zhou et al, 2013). An alternative approach to derive this multiplier directly, is to consider the work required to lift the soil that is displaced by the incrementally advancing ball.…”
Section: Experimental Procedures Preparation Of Clay Specimenmentioning
confidence: 99%
See 4 more Smart Citations
“…Merifield et al, 2009;White et al, 2010;Chatterjee et al, 2012;Zhou et al, 2013). An alternative approach to derive this multiplier directly, is to consider the work required to lift the soil that is displaced by the incrementally advancing ball.…”
Section: Experimental Procedures Preparation Of Clay Specimenmentioning
confidence: 99%
“…This is critical for the design of almost all shallowly embedded offshore infrastructure (Puech et al, 2010) including subsea pipelines, steel catenary risers and mudmats. Large-deformation finite-element (LDFE) analyses on a T-bar (White et al, 2010;Tho et al, 2012), spudcan (Hossain et al, 2005) and ball penetrometer (Zhou et al, 2013) have shown that the transition depth from N b-shallow to N b-deep is dependent on the dimensionless strength ratio s u /c9D, where c9 is the effective unit weight of the soil and D is the diameter of the penetrometer. Higher strength ratios are associated with a delay in the transition to a steady N b-deep .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations